ROLE OF COMBINATION CASEIN AND LACTOFERRIN BOVINE’S COLLOSTRUM AS A PULP CAPPING ON MACROPHAGE EXPRESSION IN MALE WISTAR RATS - Ningtyas, Endah Ariyati Eko; Santoso, Oedijani; Sadhana, Udadi; Sunarintyas, Siti (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
ABSTRACTBackground: Inflammatory and/or non-inflammatory processes play a role in stimulating pulp repair and the formation of hard tissue, namely reparative dentin. Macrophages play a role in the pathogenesis and chronic inflammatory disorders. The combination casein lactoferrin of bovine colostrum as an immunomodulator has therapeutic potential. This study aims to determine the therapeutic effect and duration of application of the combination of casein lactoferrin of bovine colostrum, on the expression of macrophages as pulp capping.Method: This study was a true experimental laboratories post test only control group design, consisting of three groups of 60 male wistar rats with 4 observation times, namely day to day 7, 14, 21 and 28 each of 5 mice. The maxillary 1st molars were prepared until the roof of the pulp was exposed. Three groups, namely the combination of casein and lactoferrin bovine colostrum (CKL) and calcium hydroxide (K1) and the untreated group (K0). Each group was filled with glassionomer as a permanent restoration. The tissue was made histological preparations with hematoxylin-eosin staining and the number of macrophages were counted, then analyzed by two way ANOVA and post hoc LSD tests.Result: The results showed that the therapeutic effect and duration of application of the combination of casein and lactoferrin bovine colostrum on the expression of macrophages as pulp cappingConclusion: The combination of casein and lactoferrin of bovine colostrum as capping material can increase the number of macrophages in the healing process of dental pulp.